Amniotic membrane and placental histopathological findings after open and fetoscopic prenatal neural tube defect repair. (10th February 2019) - Sanz Cortes, Magdalena; Castro, Eumenia; Sharhan, Dina; Torres, Paola; Yepez, Mayel; Espinoza, Jimmy; Shamshirsaz, Alireza A.; Nassr, Ahmed A.; Popek, Edwina; Whitehead, William; Belfort, Michael A.
Abstract: Objectives: To describe and compare placental and amniotic histology in women who underwent a fetoscopic myelomeningocele repair to those who underwent an open hysterotomy myelomeningocele repair. Also, we intended to compare findings from both prenatal repair groups to age‐matched control pregnant patients. Methods: Placental and membrane histopathology from 43 prenatally repaired spina bifida cases (17 fetoscopic and 26 open) and 18 healthy controls were retrospectively assessed. Quantitative assessment of histopathology included apoptosis count and maternal and fetal underperfusion scores. Qualitative assessment included the detection of pigmented macrophages and/or signs of placental/amniotic inflammation. Associations between the duration of surgery or the duration of CO2 insufflation and quantitative histological parameters were tested. Results: Fetoscopic surgery cases did not show significant differences in any of the studied parameters when compared against controls. No differences were detected either when compared with open repaired cases, except for lower proportion of pigmented laden macrophages in the fetoscopic group (11.8% vs 61.5%, P  < 0.01). No associations between the duration of surgery or the duration of CO2 exposure and any of the quantitative histological parameters were detected. Conclusions: These preliminary results support the lack of detrimental effects of the use of heated and humidified CO2 gas for uterine insufflation to fetal membranes and placenta. Abstract : What's already known about this topic? Prenatal fetoscopic myelomeningocele repair shows comparable neurosurgical outcomes with the open repair approach (standard of care), with improved perinatal results. The main drawback of the fetoscopic approach is the concerns for fetal acidosis due to CO2 exposure. So far, the effects of this approach on membranes and placenta had not been assessed. What does this study add? This study shows how there are no significant differences in apoptosis count, signs of maternal or fetal underperfusion, and inflammation or pigmented laden macrophages after fetoscopic repair when compared against controls. Fetoscopic cases did not show differences compared with open repaired cases except for lower pigmented laden macrophages, suggestive of increased intraoperative blood loss in the latter.